EXPLORATION OF SYMBIOTIC RELATIONSHIP: INVESTIGATING THE PHYSIOLOGICAL AND MICROBIOLOGICAL ACTIVITY OF SUGAR-CANE PRESS-MUD AND HARNESSING AS BIOLOGICAL MANURE. (International Journal of Food and Nutritional Sciences, 2022)
Bio-compost is a material which contains live micro-organisms exhibiting beneficial characteristics towards the growth of plants and also in soil development making the soil more fertile. Bio- composting of sugar-cane press-mud is a composition of Organic fertilizer and Bio- fertilizers where a unprocessed biological nature. i.e., plant material and living micro-organisms which are agriculturally useful in terms of nitrogen fixation, phosphorus solubilisation or nutrient mobilization have been altered together through mobilization have been altered together through microbiological decomposition processes increase the productivity of the soil or crop. Bio-Composting is the degradation of organic matter by various microbes in a moist, favourable environment. Composting takes place aerobically or an-aerobically in the environment. Five different varieties of plants were grown for enumeration of the quality of the bio-compost prepared in the trial windrow. The varieties of plants grown were namely Tomato, Chili, Cabbage, Brinjal. The Bio-compost was prepared in farm by sugarcane wastes such as bagasse and the dried sludge from Sugar Effluent Treatment Plant was mixed with it. Aerobic condition was maintained by regular tumbling of the trial bio-compost windrow and continuous monitoring of Temperature, pH and Electrical conductivity was done. Physico-chemical and microbiological results were performed once a week or as and when required. After proper degradation of the bagasse the bio-compost was used in the cultivation of the plants in selected plot. The essential factors such as N: P: K was maintained by the selected strains of micro-organisms and it was also checked that no pathogenic activity by any microbes occurred while preparation of the bio-compost.